On the gnoseological qualifications of the present discourse of the coronavirus pandemic - Hakobyan, Gevorg (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
In the article is attempted to expose the present discourse of the coronavirus pandemic to gnoseological qualification. The analysis mostly focuses on the problem of evaluating with the corresponding characterizations of the mental structures that are presented as univocal true. Emanating from researches of the philosophy of science and medicine, it is argued that all statements of the present discourse of the coronavirus pandemic, which simultaneously claim to be scientific and true, turn into antipodes of true.